Karakteristik Sifat Kuat Geser Tanah Gambut di Wilayah Rawa Melalui Analisis Hasil Uji Triaksial - Hartini, Hartini; Sutama, Adji; Arfan, Muhammad (Universitas Muhammadiyah Palembang, 2025)
The characteristics of peat soil are different from clay soil. Physically it has a high water content, large pore number, has organic material content, the presence of fibers in peat soil, while technically it has high compression and low shear strength. This study was to determine the shear strength of peat soil in North Indralaya in Bakung and Tanjung Pule villages. The soil sample used was undisturbed soil. The tool used was a triaxial test tool with CU conditions. The soil sample had a diameter of 35 mm and height of 70 mm with a sample depth of 50 cm. The sampling method used was the block sampling method. From the results of the study, it was found that the greater the isotropic consolidation stress given to the test sample, the greater the deviator stress that arose. The cohesion value was 14–22 kPa, the friction angle was 7°–8°, for effective soil 15–25 kPa. The effective internal friction angle was 7°–9°. Meanwhile, the largest peat soil shear strength value is in Tanjung Pule village with a total shear strength value of 22.636 kPa and an effective shear strength of 26.166 kPa, while Bakung village has a total shear strength of 15.593 kPa and an effective shear strength of 18.273 kPa.